Diagnostic imaging of malignant melanoma - Sielużycka, Joanna (Contemporary Oncology/Współczesna Onkologia, 2003)
Cancer imaging is increasingly identified as a specialist field within radiology, reflecting a growing need to evaluate the status of the disease, not just at the time of diagnosis and staging, but also at regular intervals during follow-up. When evaluating patients with cancer, the radiologist must understand not only the imaging modalities available but the disease and the therapeutic problems they present. The aim of this study is to evaluate diagnostic imaging of malignant melanoma. In diagnostic imaging of early stage malignant melanoma it is very important to evaluate the regional lymph node. In clinical practice, the cross-sectional imaging modalities including computed tomography (CT), ultrasound and magnetic resonance (MR) are widely used to assess lymph nodes. Soft tissue, including skin, and subcutaneus metastases, are common and characteristic of melanoma. Although usually diagnosed clinically, these deposits are often readily visualized using ultrasound and CT. These are followed by lung, liver, brain, and bone metastases. In CT examination macroscopic deposits of malignant melanoma usually appear as hyperdense. Both central and ring enhancement is typical. The usual appearances of malignant melanoma on magnetic resonance images include melanotic and amelanotic patterns. In the amelanotic pattern, the lesion is hypointense or isointense to the cortex on T1-weighted images and hypointense or isointense to the cortex on T2-weigthed images. Skeletal metastases from malignant melanoma are generally lytic. Melanoma can metastasize to the gastrointestinal tract, gallbladder, heart, breast and the urinary tract. Radiological techniques employed in the assessment of tumour response can provide information on the changes in tumour size and composition. Conventional radiology, ultrasound, CT, MR and radionuclide studies all have place in evaluating the treatment.